Factors that affect the spatial and temporal distribution of nitrate in a free aquifer of an agricultural plain basin - Calvi, Carolina Maria Rosa (2020)
The behavior of nitrate in shallow aquifers depends on several factors, such as geomorphology, soil type, thickness of the vadose zone, and its lithology, sampling period, among others. In the free aquifer of the basin of the La Ballenera creek in southeastern of Buenos Aires province, Argentina, nitrate varies in a range between 4 and 250 mg/L in samples taken in spring and winter. This basin has a large agricultural production where fertilizers are applied, and nitrates come from them. Statistical analysis of the data allow to make conclusion about the main factors that influence the variation of the nitrate content in aquifers, in this case are the lithology and the thickness of the vadose zone, related to the different transit times. The results obtained can be extrapolated to analogous basins, considering that in the spatial analysis of nitrates the heterogeneities of the system should be considered. The importance of characterizing a system with more than one sampling at several sufficiently spaced times is emphasized.